Confirmation of MRI anatomical measurements as endophenotypic markers for bipolar disorder in a new sample from the NIMH Genetics of Bipolar Disorder in Latino Populations study. (30th January 2016) - Sandoval, Hugo; Soares, Jair C.; Mwangi, Benson; Asonye, Stephanie; Alvarado, Luis A.; Zavala, Juan; Ramirez, Mercedes E.; Sanches, Marsal; Enge, Luke R.; Escamilla, Michael A.
Abstract: The main objective of this study is to establish potential neuromorphometric differences which might act as markers of genetic risk for bipolar disorder and therefore serve as endophenotypes for discovery of genes that contribute to bipolar disorder. Magnetic resonance imaging (MRI) was used to assess structural brain volumes of 49 subjects. Volumetric analyses were first performed to test possible differences in the volume of brain structures between subjects with bipolar disorder type I (BPI) and control subjects in a new sample, based on regions previously reported in the literature as being either increased or decreased in size in bipolar patients. Subsequently, for those brain regions showing statistical difference between subjects with BPI and control subjects in our new sample, we tested whether unaffected first degree relatives (UFRs) of the BPI subjects also showed similar differences compared with controls. Four specific regions (right prefrontal, right middle prefrontal, right globus pallidus and left globus pallidus) met criteria for being possible endophenotypes for BPI in this sample. Highlights: Magnetic resonance imaging can provide measurable biological markers of vulnerability to bipolar disorder. These markers satisfy some of the key criteria for being endophenotypes of bipolar disorder. The right prefrontal cortex and the right and left globus pallidum.